PENGARUH PROFITABILITAS, LEVERAGE DAN PRODUKTIVITAS TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE TAHUN 2020-2022 - Nathanael Fransiskus Mangile; Batara Daniel Bagana,SE.,M.M. (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
The stock exchange is the market where trading in stocks, bonds and other financial instruments takes place. The stock exchange is a place where companies can issue shares to obtain funds from investors, and investors can buy shares as a form of company ownership and benefit from changes in share prices. This study aims to measure how significant the influence of Profitability, Leverage and productivity is in determining bond ratings in manufacturing companies in 2020-2022. The sample in this study is a manufacturing company that issues bonds and is rated by PEFINDO (Indonesian Rating Agency), uses the rupiah currency in presenting the company's financial statements, and publishes complete audited financial statements. The data source used comes from the official website of the Indonesia Stock Exchange (IDX), namely www.idx.co.id and the bond rating database accessed from PTPEFINDO (www.pefindo.com). The conclusion of this study is that profitability has a positive effect on bond ratings, leverage has a negative effect on bond ratings and productivity has no effect on bond ratings. Keywords: Profitabilitas, Obligasi, Leverage, Produktifitas